Evaluating efficiency levels comparatively: Data envelopment analysis application for Turkish textile and apparel industry - Canan Saricam; Nazan Erdumlu (Journal of Industrial Engineering and Management (JIEM), 2012)
Purpose: The purpose of this study is to show the usage of DEA in efficiency measurement. Design/methodology/approach: The efficiencies of textile and apparel companies were analyzed by input-oriented DEA model under variable return to scale assumption. The textile and apparel companies quoted in Istanbul Stock Exchange for the period 2003 and 2008 were evaluated in terms of efficiency level providing a framework for the calculation of input excesses and output shortages. Findings: The analysis revealed that the average efficiency scores of the apparel industry was higher than the textile industry and two industries together. The companies in the apparel industry should overcome the lack of insufficient level of exports whereas the textile industry needs to increase gross value added in order to be more efficient. Research limitations/implications: Because of missing data, four companies from textile industry and one company from apparel industry were ignored although they took place in the records of Istanbul Stock Exchange. Practical implications: This study provided a framework for DEA application in determination and comparison of efficiency performance in an industry level. Originality/value: Selecting the groups compared as textile industry, apparel industry and the two industries in general allowed discussing the comparative efficiencies of two industries eliminating the industry specific pitfalls.
Keywords: 650; data envelopment analysis; textile industry; apparel industry; efficiency measurement